Film Animasi 2D Peristiwa Perobekan Bendera di Hotel Yamato dengan Teknik Parallax - Amelia Agustina Herlijanto; Edbert Christian Wenata (Institut Seni Indonesia Yogyakarta, 2025)
2D Animation Film About Flag Ripping Incident at Yamato Hotel Using Parallax Technique. The flag-tearing incident at the Yamato Hotel in 1945 was one of the most important heroic stories in Indonesia’s history, particularly for the city of Surabaya. However, the rapid flow of globalization has caused historical stories like this to become less known and less appreciated by the younger generation. To address this challenge, a 2D animated film was created as a visual communication medium aimed at increasing young people's interest in national history. A modern anime visual style was used to appeal to younger audiences, and the parallax technique was implemented in the animation production to create the illusion of depth and an artistic, dynamic perspective. Parallax is a technique that separates visual elements into several layers, which are moved at different speeds to simulate depth. This technique was applied during the production phase and proposed as a visual solution to make historical narratives feel more alive and engaging. The research method used covering pre-production, production, and post-production stages. Based on a survey conducted after the film's publication on YouTube, it was found that the use of parallax in the animated film added visual depth and made the imagery more dynamic.